Seroprevalence Of Peste Des Petits Ruminants In Small Ruminants Under Different Managemental Conditions - Chauhan, H. C.; Dadawala, A. I.; Chandel, B. S.; Kalyani, I. H.; Patel , Sandip S.; Kher , H. N. (Indian Journal of Veterinary Sciences and Biotechnology, 2011)
The present study envisaged appraisal of seroepidemiology of PPR in sheep and goats maintained under different managemental conditions. Among 970 sera of sheep and goats, 503 showed positive antibody titre indicating 51.86 per cent seroprevalence, where in seroprevalence was found to be increased with increase in the age and highest seroprevalence was recorded in the panjarapoles, followed by migratory flocks and organized farms. Out of 591 sera tested from sheep, 335 (56.68 %) were found to be positive for antibodies against PPRV. Agewise maximum seroprevalence recorded was age groups of > 3 years followed by 63.41 per cent in age group of 2 to 3 years, 42.05 per cent in 1 to 2 years and 35.71 per cent in < 1 year. Out of 379 serum samples examined from goats, 168 (44.33 %) showed the positive reaction to PPRV. Maximum seroprevalence of 55.65 per cent was found in the age group of > 3 years, followed by 2 to 3 years (52.00 %), 1 to 2 years (31.91 %) and 27.87 per cent in < 1 year of age groups as reported in case of sheep.
Keywords: Seroprevalence; PPRV; c-ELISA; Management; Gujarat